Functionalized Graphene Oxide Thin Films for Anti-tumor Drug Delivery to Melanoma Cells - Sima, Livia E.; Chiritoiu, Gabriela; Negut, Irina; Grumezescu, Valentina; Orobeti, Stefana; Munteanu, Cristian V. A.; Sima, Felix; Axente, Emanuel (Frontiers in Chemistry, 2020)
Since its discovery, Graphene and the associated derivate nanomaterials, Graphene Oxide (GO) and reduced-GO were in the forefront of continuous developments in bio-nano-technology due to their unique physical-chemical properties. Although GO was proposed as drug release matrices for cancer cells targeting, there is still a great concern when using these nanomaterials due to cytotoxicity issues, mainly with respect to normal cells within tissues. In this study, we report on the fabrication of functional GO bio-interfaces (drug carriers) by Matrix-Assisted Pulsed Laser Evaporation (MAPLE) for targeting melanoma cells. We first addressed a detailed comparison between GO and protein functionalized GO when submitted to in vitro cytotoxicity assay. Bovine Serum Albumin (BSA) was used for the noncovalent GO surface conjugation. Safe concentration windows were identified by live/dead staining and MTS assays for five different human melanoma cell lines, while melanocytes and human dermal fibroblasts were used as normality controls. Hybrid GO-BSA nano-scaled thin films incorporating Dabrafenib (DAB) and Trichostatin A (TSA) inhibitors for cells bearing BRAFV600E activating mutation were assembled on solid substrates by MAPLE. We demonstrate the successful laser immobilization of the drug within GO-BSA carrier matrix by the efficient activity for BRAF inhibition. DAB activity was revealed by the decreased ERK phosphorylation in primary melanoma (amelanotic SKmel28 BRAFV600E cell line), while the epigenetic inhibitor TSA induce acetylated histones accumulation in cell’s nuclei (pigmented SKmel23 BRAF wt cell line). Moreover, melanoma cells exposed to coatings with gradient concentration of inhibitors evidenced a dose-dependent effect. Such functional bio-platforms could present high potential for the cell-biomaterial interface engineering in personalized cancer therapy studies.